Straight Skin, Gay Masks and Pretending to Be Gay on Screen - Padva, Gilad (Routledge, 2020)
Straight Skin, Gay Masks and Pretending to Be Gay on Screen examines cinematic depictions of pretending-to-be-gay, assessing performances that not only reflect heteronormative and explicitly homophobic attitudes, but also offer depictions of gay selfhood with more nuanced multidirectional identifications. The case of straight protagonists pretending to be gay on screen is the ideal context in which to study unanticipated progressivity and dissidence in regard to cultural construction of human sexualities in the face of theatricalized epistemological collapse. Teasing apart the dynamics of depictions of both sexual stability and fluidity in cinematic images of men pretending to be gay offers new insights into such salient issues as sexual vulnerability and dynamics and long-term queer visibility in a politically complicated mass culture which is mostly produced in a heteronormative and even hostile cultural environment. Additionally, this book initially examines queer uses of sexuality masquerade in Alternate Gay World Cinema that allegorically features a world pretending to be gay, in which straights are harassed and persecuted, in order to expose the tragic consequences of sexual intolerance. Films and TV series examined as part of the analysis include The Gay Deceivers, Victor/Victoria, Happy Texas, William Friedkin’s Cruising and many other straight and gay screens. This is a fascinating and important study relevant to students and researchers in Film Studies, Media Studies, Gender Studies, Queer Studies, Sexuality Studies, Communication Studies and Cultural Studies.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé